Síndrome de burnout y su impacto en el rendimiento laboral del personal de enfermería del servicio de emergencia Hospital Básico Yaguachi, Guayas noviembre 2023- abril 2024. - Águila Estrada, Ximena Jaqueline (2024)
According to the World Health Organization (WHO), Burnout syndrome is defined as the "result of chronic stress in the work environment that has not been managed effectively". The WHO specifies that this term refers specifically to work situations and should not be used to describe experiences in other areas of life. The most distinctive symptoms include emotional exhaustion, depersonalization and diminished self-fulfillment, with healthcare workers being one of the professions most at risk. A descriptive, explanatory and field research methodology was used to determine the prevalence of Burnout syndrome among health personnel at the "Doctor José Cevallos Ruiz" Hospital in Yaguachi during the period November 2023 and April 2024. Analyses of various aspects such as age, profession, among others, were carried out. In addition, the Maslach questionnaire was used as an evaluation instrument, which addresses three dimensions: emotional exhaustion, depersonalization and personal fulfillment. With regard to quantitative data, we chose to use the Maslach Burnout Inventory (MBI), developed by Cristina Maslach in 1981. The Spanish version was created by Nicolás Seisdedos in 1997.This questionnaire consists of 22 questions designed to capture the feelings and thoughts of the population under study. The analysis carried out focused on a descriptive and explanatory approach, based on a field research design.